2022
DOI: 10.4093/dmj.2021.0092
|View full text |Cite
|
Sign up to set email alerts
|

GPR40 Agonism Modulates Inflammatory Reactions in Vascular Endothelial Cells

Abstract: Endothelial dysfunction is strongly linked with inflammatory responses, which can impact cardiovascular disease. Recently, G protein-coupled receptor 40 (GPR40) has been investigated as a modulator of metabolic stress; however, the function of GPR40 in vascular endothelial cells has not been reported. We analyzed whether treatment of GPR40-specific agonists modulated the inflammatory responses in human umbilical vein endothelial cells (HUVECs). Treatment with LY2922470, a GPR40 agonist, significantly reduced l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 19 publications
(21 reference statements)
0
6
0
Order By: Relevance
“…LY2922470 is a GPR40 agonist that has shown an effective and persistent dose‐dependent reduction in glucose levels and a significant increase in insulin and GLP‐1 secretion in preclinical trials 653 . GPR40 agonists might also regulate inflammatory responses and thus play a role in improving the development of diabetes complications 654,655 …”
Section: Antidiabetic Drugsmentioning
confidence: 99%
See 1 more Smart Citation
“…LY2922470 is a GPR40 agonist that has shown an effective and persistent dose‐dependent reduction in glucose levels and a significant increase in insulin and GLP‐1 secretion in preclinical trials 653 . GPR40 agonists might also regulate inflammatory responses and thus play a role in improving the development of diabetes complications 654,655 …”
Section: Antidiabetic Drugsmentioning
confidence: 99%
“… 653 GPR40 agonists might also regulate inflammatory responses and thus play a role in improving the development of diabetes complications. 654 , 655 …”
Section: Antidiabetic Drugsmentioning
confidence: 99%
“…7,8 In addition to T2DM, studies have shown that GPR40 is also a potential target for the complications of T2DM and metabolic syndrome (MetS) such as nonalcoholic fatty liver disease (NAFLD) and cardiovascular diseases. [9][10][11][12][13][14] A large number of studies have shown that GPR40 is expressed by not only pancreatic β-cells, but also various types of cells including macrophage, 15 vascular endothelial cell, 14 hepatocyte, 16,17 and fibroblast. 15 Consistently, many studies have shown that GPR40 has anti-inflammatory properties that contribute to improvement of complications of T2DM and MetS.…”
Section: Introductionmentioning
confidence: 99%
“…Agonists of GPR40 have been shown to reduce neuronal damage caused by Alzheimer's disease GPR40 [15]. LY2922470, a novel small-molecule GPR40 activator, has been demonstrated to be a viable treatment option for type 2 diabetes due to its ability to stimulate insulin production [16][17][18]. However, whether LY2922470 has shown protective effects against ischemic stroke and cerebral I/R injury remains unknown.…”
Section: Introductionmentioning
confidence: 99%